A better start to literacy for bilingual children in New Zealand: Findings from an exploratory case study in te reo Māori and English - Denston A; Martin R; Gillon G; Everatt J (Taylor and Francis Group, 2024)
This article details findings from an exploratory case study that examined the efficacy of a phonological awareness and vocabulary programme with children educated in a bilingual immersion context of English and te reo Māori (Māori language) in Aotearoa New Zealand. The current paper discusses changes in the development of early literacy skills in English and te reo Māori in two groups of children aged from 5 years 0 months to 7 years 5 months. Twenty-six children from two bilingual classrooms in a rural school participated in a programme implemented by teachers over 15 weeks. The programme included explicit instruction in phonological awareness and vocabulary. One classroom was from Level 1 te reo Māori immersion, and one was from Level 3 te reo Māori/English. Results were analysed at cohort and class levels. Analyses indicated that both groups of children significantly improved in phonological awareness skills, non-word reading, and expressive vocabulary. Correlational analyses indicated that growth in te reo Māori skills was positively associated with growth in English skills. These findings suggest that further investigation into how the explicit teaching of te reo Māori can benefit the development of phonological awareness and print-related skills in English.
Keywords: Bilingual Education; Indigenous Language; Minority Language; Te Reo Māori